Translating Taboo Language in Joyce’s Ulysses: A Special Edition in Spanish for Franco and Perón. - Sanz Gallego, Guillermo (Atlantis. Journal of the Spanish Association for Anglo-American Studies, 2013)
In the years following its publication in 1922, James Joyce’s Ulysses inspired great controversy. It was banned in much of the English-speaking world because of a number of passages considered pornographic. Paradoxically, Ulysses was never banned in Spain during the Franco regime, nor was it in Argentina during the regimes of Ramírez and Perón. This contrast is puzzling, given the strong censorship policies in both countries during the first part of the twentieth century. The reason Joyce’s work was not banned in the Spanish-speaking world may be found in several crucial differences between the original text in English and its first Spanish translation. A comparison of the passages in English marked as objectionable by the US censor and Salas Subirat’s first translation of them into Spanish shows a series of shifts that produce a lack of equivalence and accessibility, as well as fragments of text omitted by the translator.